PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. NASMOCO PEMUDA SEMARANG SECTION BENGKEL - Ghassani Mutiara Ramadhani; Saryadi Saryadi; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
section, have responsibility to achieve organization’s goals. Performance of organization really depends on abilities and competencies of those. PT. Nasmoco Pemuda Semarang is a private institution that is engaged in the automotive field and has several business areas, namely the sales of cars, sales of spare parts and maintenance or servicing section periodically, which is required to always serve the needs of customers by providing best services in order to increase quantity of cars which entrust PT. Nasmoco as a partner for servicing. However, in 2013 there was unachieved the target units in the section service. Moreover, Transformational Leadership that implemented by the head of section service had not been able to improve Work Discipline at PT. Nasmoco Pemuda Semarang, especially in servicing section.This study aims to determine the effects of Transformational Leadership, Organizational Culture, and Work Discipline toward the Employee Performance. This study uses census method with a sample of 70 employees that will be investigated. Data were analyzed through the validity, reliability, crosstab, product moment correlation, coefficient of determination, simple linear regression, multiple linear regression, t test and F test.The result shows that Transformational Leadership has significant effect on the Employee Performance. Work Discipline has significant effect on the Employee Performance and Organizational Culture significantly influences the employee performance. Simultaneously, the Transformational Leadership, Discipline Work and Cultural Organization have significant effect on the Employee Performance. Based on the multiple regression test, the results of beta coefficient figures show 0.226, 0.271, and 0.421, for Transformational Leadership, Work Discipline, and Cultural Organization respectively. Organizational Culture provides the most impact on employee performance.Based on the research result, it suggested to improve Transformational Leadership could be executed by improving the ability of the leadership in getting closer to his employees. Moreover, the improvement of Work Discipline could be achieved by providing appreciation and improving control. The improvement of Organizational Culture could be performed by working more excited. Through of these, at PT. Nasmoco Pemuda Semarang Section Service, the expected level of performance of employees will increase.